Persepsi, Sikap Dan Perilaku Masyarakat Nelayan Terhadap Pt. Aquafarm Nusantara Di Desa Pardamean Ajibata Kecamatan Ajibata Kabupaten Toba Samosir Provinsi Sumatera Utara - Nova Wulan Sari Lubis; Darwis AN; Ridar Hendri (Jurusan Sosial Ekonomi Perikanan, 2020)
This survey research was conducted in Pardamean Ajibata Village, Ajibata District, Toba Samosir Regency, North Sumatra Province, from May 15 till May 30, 2019. The purpose of this study was to determine: the perception of fishing communities towards PT. Aquafarm Nusantara; the attitude of the fishing community towards PT. Aquafram Nusantara; and the behavior of the fishing community towards PT. Aquafarm Nusantara. Research respondents were 39 fishermen taken using the Slovin formula. The results showed that all fishermen had a bad perception of PT. Aquafarm Nusantara is based on water quality and catchment area. Fishermen reject the establishment of PT. Aquafarm Nusantara in Lake Toba Waters. The rejection action for the past 8 years, is as much as 5 times. Fishermen leak the floating net cages of PT. Aquafarm Nusantara when fishermen's fish catch is not sufficient for their basic needs.